Optimizing ZISWAF as a Social Safety Nets: A Lesson from COVID-19 Pandemic - Paksi, Girindra Mega; Indraswari, Citra Rahayu; Kadji, Dzuliyati; Aulia, Dynda Fadhlillah (Laboratorium Riset Ekonomi, 2024)
Introduction: Safety nets are needed in the economic and non-economic sectors to overcome the adverse effects of the disaster. The past COVID-19 pandemic has shown the importance of a safety net to prevent extreme poverty due to disasters. In this case, ZISWAF assets should be used as a safety net to prevent a decline in people's welfare due to various disasters that will occur in the future. Therefore, this study aims to explore the potential of ZISWAF assets as a safety net in the future Methods: This study uses the Literature Review method, comparing various result from researches to form a comprehensive review Results: The study results show that ZISWAF assets in the past have been used to improve people's welfare. However, there seems to be a paradigm shift today where ZISWAF, particularly in Indonesia, is only used to fulfill worship purposes, not to encourage people's welfare. Several potential method is available to be used as choices to optimize ZISWAF Conclusion and suggestion: It is hoped that innovations will be made to utilize ZISWAF assets to be used as a social safety net in the future to optimize ZISWAF